RETRAINING DAN PENDAMPINGAN PERGURUAN TINGGI DALAM UPAYA OPTIMALISASI PENGGUNAAN RAPORT KESEHATAN REMAJA DI SMPN I SOCAH KABUPATEN BANGKALAN - Esyuananik Esyuananik; Anis Nur Laili; Uswatun Khasanah (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Adolescence is a period of storm and stress since adolescents experience many challenges both from themselves (biopsychosocial factors) or the environment (environmental factors). Moreover, adolescents do not have the ability to face these challenges, in which it is possible for them to end up in various health problems that are so complex as a result of the risky behavior they do (the Ministry of Health of the Republic of Indonesia, 2018). The book entitled Rapor Kesehatanku (My Health Report) contains a variety of information related to the health and development of students. Students who need further information are expected to discuss with parents, teachers or health workers from the Community Health Center (the Ministry of Health of the Republic of Indonesia, 2017). An initial survey at Bangkalan Health Office showed that Rapor Kesehatanku program for adolescents had not been running optimally due to many obstacles in the field, such as the lack of report books and the empowerment of adolescent counselors that had not been established.The method used in this community service was retraining adolescent counselors in providing health information to their peers through adolescent health report book. Each student was expected to have a health report book and be able to know their growth and development on an ongoing basis. Retraining was conducted online, considering the fact that it was still the Covid-19 pandemic, involving 31 students and 9 teachers (classroom teachers, counseling teachers and school health service/UKS teachers). All participants had previously received the module to read before the online meeting.The results of the first evaluation found that there were still students who were not able to fill in health and family health history and fill in the Body Mass Index (BMI) chart on the KMS in health report book. However, in the second evaluation, students were already able to fill in the health and family health history and fill out the BMI chart on the KMS in the health report book.In addition, retraining activities for UKS manager and instructor in implementing health literacy movement using Rapor Kesehatanku book were conducted via virtual meetings. The monitoring and implementation went well. Adolescents at SMPN 1 Socah should frequently read the health information module given and apply it in their daily life. After the Covid-19 pandemic is over and the teaching and learning process returns to normal, UKS teachers and classroom teachers should optimize Rapor Kesehatanku book in carrying out UKS activities, and coordinate with UKS officers at the Community Health Center.